Quantitative analysis of blowout preventer flat time for well control operation: Value added data aimed at performance enhancement - Khan, J.A. (Elsevier Ltd, 2021)
Flat-time operations are essential to the well construction process in the oil and gas drilling operation. However, the technical time limit (to construct the well as fast as possible for a certain set of conditions) for a well is not always achieved, which leads to increased operating costs. By reducing flat time, the cost of the well can be reduced. The safe handling of the Blowout Preventer (BOP) is one of the basic operations during the flat time period to ensure control of the well during drilling. Therefore, an example case study has been conducted using 14 wells drilled in Malaysia to determine the significance of BOP flat time versus total flat time. Findings of present study clarifies that BOP flat time has a significant impact on the total flat time. Therefore, if the BOP flat time as a total time is reduced, the cost of a well will decrease considerably. Additional research was conducted to analyze BOP flat time using 32 wells drilled in Malaysia for benchmarking purposes. The times for each BOP activity were recorded and a statistical analysis was performed. Mean times for each activity were calculated and outliers were examined. The target time for nippling up (when the BOP is installed onto the wellhead) BOP is 8 h. The target time for nippling down BOP (BOP is removed from the wellhead) is 6 h. The target time to change the BOP rams is 2 h. The target time for the pressure test change out of BOP rams is 1.5 h. The target duration of the BOP pressure test is 6 h. Based on the results of the statistical analysis, the factors affecting the BOP flat time were dependent on rig procedure, rig facilities, BOP configuration, BOP pressure rating, and BOP connection type. Â© 2020 Elsevier Ltd